2020
DOI: 10.1002/ajoc.202000181
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stereochemistry of the C30−C63 Section of Karlotoxin 2

Abstract: Karlotoxin 2 (KmTx2) is a marine natural product isolated from the dinoflagellate Karlodinium veneficum. The absolute configuration of KmTx2 was determined by NMR analysis in combination with degradation of the natural product, and the absolute configuration at C49 was revised by computational analysis. On the other hand, we reported revision of the absolute configuration of amphidinol 3 (AM3), whose structure is similar to that of KmTx2, by comparing NMR data of the synthesized partial structures and total sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…[348][349][350][351] The total synthesis of amphidinol-3 has been achieved, 352 as has that of karlotoxin-2 881, which necessitated its structural revision to that shown here. 353 Unexpected new bioactivities can be found for known compounds. The effects of brevetoxin-2 in reversing the effects of strokes in mice have been investigated.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[348][349][350][351] The total synthesis of amphidinol-3 has been achieved, 352 as has that of karlotoxin-2 881, which necessitated its structural revision to that shown here. 353 Unexpected new bioactivities can be found for known compounds. The effects of brevetoxin-2 in reversing the effects of strokes in mice have been investigated.…”
Section: Reviewmentioning
confidence: 99%
“…The total synthesis of amphidinol-3 has been achieved, 352 as has that of karlotoxin-2 881 , which necessitated its structural revision to that shown here. 353…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…Removal of the acetyl groups of 9 was carried out, giving hydroxy ketone 4 . We previously reported that removal of the acetyl groups proceeded effectively by using a solid catalyst under flow conditions . This procedure is useful for water-soluble polar products such as 4 , because enough pure material can be obtained after the concentration of the eluent without further purification.…”
mentioning
confidence: 99%